Assurance of salvation : implications of a New Testament theology of hope - Hoskinson, Matthew C., 1977- (Greenville, S.C. : Bob Jones University Press, 2010)
"This book is a study of the doctrine of assurance in light of the New Testament's teaching on hope"--Provided by publisher.
Includes bibliographical references (p. 219-228).
Keywords: Assurance (Theology) -- History of doctrines; Hope -- Biblical teaching